A DESCRIPTIVE PARADIGM OF ESCALATING ENDOVASCULAR INTERVENTION FOR THE MANAGEMENT OF TRAUMATIC CARDIAC ARREST IN A SWINE MODEL OF NON-COMPRESSIBLE TORSO HAEMORRHAGE. Issue 12 (18th November 2016) - Barnard, EB; Smith, JE; Manning, JE; Rall, JM; Cox, JM; Bebarta, VS; Ross, JD
Abstract : Objectives & Background: Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) aims to improve trauma survival by controlling torso haemorrhage. Selective Aortic Arch Perfusion (SAAP) is an experimental resuscitative technique that, in addition to controlling torso haemorrhage, allows infusion of oxygenated blood into the proximal aorta - theoretically providing coronary perfusion pressures adequate for return of spontaneous circulation (ROSC) in cardiac arrest (figure 1). Prolonged cardiac support can subsequently be achieved by converting the SAAP blood supply from exogenous to autologous via a central venous catheter–an extra-corporeal life support circuit (SAAP-ECLS). Hypotheses–1. Swine in haemorrhage-induced traumatic cardiac arrest that do not achieve a ROSC with initial therapy (REBOA), will have ROSC with more advanced therapy (SAAP). 2. Animals that do not achieve ROSC with REBOA and subsequent SAAP will achieve ROSC with SAAP-ECLS. Methods: 70–90 kg swine underwent a combination of non-compressible torso and arterial haemorrhage. Arrest was defined as a systolic blood pressure (SBP) <10 mm Hg, together with an inappropriate bradycardia. All animals initially received REBOA (inflation of zone 1 REBOA and four units of intravenous blood). Those that did not achieve ROSC (defined as SBP >50 mm Hg) subsequently received SAAP (800 ml/minute of intra-aortic oxygenated blood, up to 4000 ml). Animals that did not have a ROSC after SAAP received continuous SAAP-ECLS (at 800 ml/minute). The protocol end-point was 60 minutes from the start of the REBOA intervention. Data are descriptive, and presented as mean (+/−standard deviation) and number (percent). Results: Eight animals were included; weight 75.0 kg (+/−3.6); time from the start of the injury to onset of arrest was 9.9 minutes (+/−1.4). Two (25.0%) animals had a ROSC with REBOA, and out of the remaining six a further two (25.0%) had a ROSC with SAAP. The four remaining animals, that had not achieved ROSC with REBOA and subsequent SAAP, all had a ROSC with SAAP-ECLS (figure 2). Conclusion: A step-wise approach of more complex endovascular intervention in haemorrhage-induced traumatic cardiac arrest may be an effective clinical paradigm – in this swine model all animals had short-term survival following escalating intervention: REBOA, followed by SAAP, followed SAAP-ECLS as required.Figure 1 Figure 2